Is the manual preparation of platelet rich plasma safe? (Research, Society and Development, 2022)
The safety and sterility of Platelet Rich Plasma (PRP) produced manually concerns the scientific community, since there is a huge gap in the literature on the subject. Understanding the risks inherent to sterile handling and incorporating standard procedures is essential for patient safety, with an increasing demand for safely and effectively producing PRP without the prohibitive costs of commercial kits. The purpose of our research project is to show that through adequate training and qualification of health professionals, we can produce a low-cost, extremely safe, and effective product that fits perfectly into the reality of underdeveloped and emerging countries. We have developed a detailed step-by-step guide for standardizing the procedure for manual preparation of PRP, which ranges from the venipuncture procedure, including equipment cleaning, to the preparation of the PRP. Twenty-two PRP samples were produced and sent to an independent analysis laboratory, for identification and isolation of microorganisms through culture media. No microorganisms were identified and isolated from the samples, resulting in a contamination percentage of 0%, proving the effectiveness of the training and method in producing PRP in a safe and sterile way. Through the training of health professionals and the suggested protocols, it was possible to confirm our hypothesis that it is feasible to manually prepare contaminant-free PRP, which is safe for use in interventions where the product is recommended, without the need of commercial kits.